THE INFLUENCE OF BEAUTY INFLUENCER REVIEWS ON SKINCARE PRODUCT PURCHASE DECISIONS AMONG FISIPOL STUDENTS OF MALIKUSSALEH UNIVERSITY - Grace Sela Karisma Cintana; Nursakinah Ritonga; Lisa Iryani; Teuku Zulkarnaen; Nanda Ameliany; Cut Andyna (RADJA PUBLIKA, 2025)
This study aims to determine and analyze the influence of beauty influencer reviews on skincare product purchasing decisions among students of the Faculty of Social and Political Sciences, Malikussaleh University. This study uses a quantitative approach. The population in this study were students of the Faculty of Social and Political Sciences, Malikussaleh University who use skincare products whose exact number is unknown. Determination of the number of respondents using a non-probability sampling method with a purposive sampling technique, the calculation of the number of samples using the Lemeshow formula, so that a sample of 100 respondents was obtained. The data analysis method used in this study is simple linear regression analysis, instrument testing, classical assumption testing, and hypothesis testing, as well as the coefficient of determination with the help of the SPSS version 26 application. The results of this study indicate that the beauty influencer review variable has a positive and significant effect on purchasing decisions with a calculated t value > t table, which is 7.477 ˃ 1.984 and a significant value of 0.000 ˂ 0.05, so that Ho is rejected and Ha is accepted.